Presence of Pseudomonas Aeruginosa in drinking water of Bangladesh - Momtaz, Sumaiya Sadia (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.